Representations of Academic Life: Institutional and Personal Values - Flávia Vieira; José Carlos Morgado; Judite Almeida; Manuela Silva; Joaquim Sá (Universidad Autónoma de Baja California, 2014)
The way academics construct professional identities and operate in a complex profession that is under pressure depends on how they position themselves in relation to institutional cultures. In order to investigate faculty representations of academic life, a survey case study (questionnaire and interviews) focusing on potential dissonance between institutional and personal values was conducted at the University of Minho (Braga-Portugal), a research-teaching university. Dissonance was found related to teaching, research, working climate, relationships and leadership, suggesting a person-organization misfit. Dissatisfaction arising from values incongruence co-exists with efforts for self-fulfilment as academics struggle to preserve their identity while realizing that institutional priorities may run counter to their ideals. Acknowledging dissonance as a vital element within a culture of respect for diversity would foster the negotiation of understandings about what the academic community is and might be. Institution-specific inquiry into academic experience should not only be expanded but also become part of the strategic (re)definition of institutional development policies.